Mapping the Sustainability Consciousness of Students - Akalamkam, Kalyani (JOURNAL OF INDIAN EDUCATION, 2022)
Education plays a critical role in empowering individuals to make choices which contribute to sustainable development. The research focus in this area has shifted from environmental consciousness to a broader concept of sustainability consciousness encompassing the multiple dimensions of sustainable development. Sustainability consciousness (SC) as a construct is represented by categories of knowingness, attitude and behaviour in the three dimensions of sustainable development (SD) namely ‘environment’, ‘social’ and ‘economic’ dimensions. This study is undertaken to find out the sustainability consciousness of students (17–18 years) and analyse the relationship between various constructs and sub-constructs based on the ‘three-order theorised model of sustainability consciousness constructs. The sample constitutes 330 students who recently passed out of various schools across India. The mapping was undertaken using an empirically validated and test designed tool ‘Sustainability Consciousness Questionnaire’ (SCQ). The findings reveal that students have high level of sustainability knowingness (in all the three dimensions, but mostly in the environmental dimension) and low level of sustainability behaviour (lowest in the environmental dimension). Correlation analysis between the constructs of SC indicates positive interaction between sustainability knowingness and sustainability attitude. Sustainability behaviour is positively associated with sustainability attitude except in the areas of environment and economy indicating that environmental knowingness has not translated into attitude and further into behaviour. The study has implications for curricular and pedagogical initiatives to promote sustainability consciousness in students.